Staphylococcus aureus‐induced complement activation promotes tissue factor‐mediated coagulation. (23rd March 2018) - Skjeflo, E. W.; Christiansen, D.; Fure, H.; Ludviksen, J. K.; Woodruff, T. M.; Espevik, T.; Nielsen, E. W.; Brekke, O. L.; Mollnes, T. E.
Abstract : Essentials Complement, Toll‐like receptors and coagulation cross‐talk in the process of thromboinflammation. This is explored in a unique human whole‐blood model of S. aureus bacteremia. Coagulation is here shown as a downstream event of C5a‐induced tissue factor (TF) production. Combined inhibition of C5 and CD14 efficiently attenuated TF and coagulation. Summary: Background: There is extensive cross‐talk between the complement system, the Toll‐like receptors (TLRs), and hemostasis. Consumptive coagulopathy is a hallmark of sepsis, and is often mediated through increased tissue factor (TF) expression. Objectives: To study the relative roles of complement, TLRs and TF in Staphylococcus aureus ‐induced coagulation. Methods: Lepirudin‐anticoagulated human whole blood was incubated with the three S. aureus strains Cowan, Wood, and Newman. C3 was inhibited with compstatin, C5 with eculizumab, C5a receptor 1 (C5aR1) and activated factor XII with peptide inhibitors, CD14, TLR2 and TF with neutralizing antibodies, and TLR4 with eritoran. Complement activation was measured by ELISA. Coagulation was measured according to prothrombin fragment 1 + 2 (PTF1 + 2 ) determined with ELISA, and TF mRNA, monocyte surface expression and functional activity were measured with quantitative PCR, flow cytometry, and ELISA, respectively. Results: All three strains generated substantial and statistically significant amounts of C5a, terminal complement complex, PTF1 + 2, and TF mRNA, and showed substantial TF surface expression on monocytes and TF functional activity. Inhibition of C5 cleavage most efficiently and significantly inhibited all six markers in strains Cowan and Wood, and five markers in Newman. The effect of complement inhibition was shown to be completely dependent on C5aR1. The C5 blocking effect was equally potentiated when combined with blocking of CD14 or TLR2, but not TLR4. TF blocking significantly reduced PTF1 + 2 levels to baseline levels. Conclusions: S. aureus ‐induced coagulation in human whole blood was mainly attributable to C5a‐induced mRNA upregulation, monocyte TF expression, and plasma TF activity, thus underscoring complement as a key player in S. aureus ‐induced coagulation.